Türk Basınına Göre Geçici Irak Hükümet Konseyi’nin Oluşum Sürecinde Irak Türkmenleri ve Türkiye - Aydın YİĞİT (Gazi Akademik Bakış)
In the 2003 Iraq war the US and Coalition Forces acted together with opposition groups, instead of with Turkey, which had decided not to become involved in the war. However, one of the opposition groups were the Turkmen and they continued to be a factor taken into account during the period of continuous negotiations between the USA and Turkey, although they began to be ignored after the March 1 Motion rejection. One of the most important indicators of this was the Interim Iraqi Governing Council (IGC), which was formed after the war. During the formation of this council and the first cabinet of Iraq, the Turkmen were neither represented in proportion to their populations, nor were they brought into positions where they would be effective in terms of the administration. Within this context, the situation, attitude and behavior of the Iraqi Turkmen are the main topics to be examined prior to the 2003 Iraq War, during the war and during the reconstruction of Iraq, employing the Turkish press and related sources. In this context, events such as the London, Selahattin, Ankara, Nasiriye and Baghdad Meetings, the IGC and the formation of the Iraqi Cabinet are here evaluated in relation to the Turkmen